Novel approach to overcome the β-lactam resistant bacteria using an actinobacterial inhibitory protein - Nada A. M. Abdelbary; Rawia F. Gamal; Waleed M. Abdulkhair; Sawsan Y. Elateek (Novel Research in Microbiology Journal, 2023)
β-lactam resistance is a serious problem that the hospitals face worldwide; particularly in the developing countries. The widespread of this resistance is attributed to various mechanisms used by the nosocomial bacteria. The aims of this study were to monitor the spread of the β-lactam resistant bacteria in the different provinces of Egypt; to create a biocontrol strategy by producing the β-lactamase inhibitory protein from the Streptomyces bacteria, and to knowing its suitability for the human use. Seventy β-lactam resistant bacterial isolates were sampled randomly from several hospital laboratories across ten governorates of Egypt. The isolates were screened against six different antibiotics; mainly Amoxicillin; Amoxicillin-Clavulanate, Penicillin, Ampicillin-Sulbactam, Cefepime, and Piperacillin-Tazobactam at 250 µg/ ml, and their Minimum inhibitory concentration (MIC) was recorded. The Bn67 isolate was the most promising isolate, which was molecularly identified using 16SrRNA partial sequence as Pseudomonas aeruginosa (LC710315.1). So in order to overcome this bacterial resistance; eighty actinobacteria were isolated from several soil samples collected from Giza governorate, Egypt, and were screened for their effectiveness against Bn67. The actinobacterial isolate (Stn-01) showed the maximum inhibitory efficacy against Bn67 and was identified using 16SrRNA partial sequence as Streptomyces katsurahamanus (LC710314.1). The inhibitor protein (β-LIP-n) was isolated; precipitated, and purified to give 35 kDa with 17 amino acid sequences. The β-LIPn exhibited no cytotoxic potential against the Human Skin Fibroblast (HSF) cell line at 200 µg/ ml. This approach of using the bacterial soil-based inhibitor protein to biocontrol the β-lactam resistant bacteria is considered as novel and as a promising start-up to using the environmental bacteria to overcome this problem of β-lactam resistance.